2015
DOI: 10.1097/ipc.0000000000000253
|View full text |Cite
|
Sign up to set email alerts
|

Visual Indicators on Vaccine Boxes as Early Warning Tools to Identify Potential Freeze Damage

Abstract: BackgroundThe aim of this study was to determine whether the use of visual freeze indicators on vaccines would assist health care providers in identifying vaccines that may have been exposed to potentially damaging temperatures.MethodsTwenty-seven sites in Connecticut involved in the Vaccine for Children Program participated. In addition to standard procedures, visual freeze indicators (FREEZEmarker® L; Temptime Corporation, Morris Plains, NJ) were affixed to each box of vaccine that required refrigeration but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Vaccine vial monitors trace if the vaccine has suffered cumulative heat impact by showing clear visual change; the reactions vary in accordance with the category of vaccine to which they are assigned [ 14 ]. Visual freeze indicators provide a visual indication of exposure to freezing [ 23 ]. Additionally, the “shake test” enables visual detection of whether an aluminium-based freeze-sensitive vaccine has been affected by freezing [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Vaccine vial monitors trace if the vaccine has suffered cumulative heat impact by showing clear visual change; the reactions vary in accordance with the category of vaccine to which they are assigned [ 14 ]. Visual freeze indicators provide a visual indication of exposure to freezing [ 23 ]. Additionally, the “shake test” enables visual detection of whether an aluminium-based freeze-sensitive vaccine has been affected by freezing [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…While we did not identify disruptive temperature gradients created by the thermal ballast loading strategies employed in this study, careless placement of water bottles may unfavorably disrupt refrigerator airflow, exacerbating existing temperature gradients, or creating new ones. Furthermore, most users utilize a single temperature monitoring probe inside their vaccine refrigerators, and so may fail to detect these types of problems [36]. In addition, space constraints imposed by use of even moderate thermal ballast loads could lead to cramped vaccine storage conditions and complicate inventory management.…”
Section: Discussionmentioning
confidence: 99%
“…However, actual numbers might be higher considering that our observations focused only on visible logbooks. Regarding the location of temperature-monitoring devices, a study in the US reported that 86.0% positioned their temperature-monitoring device not in the center but rather at the front of the refrigerator (51.2%) [28]. Actual contact of vaccine boxes with outer walls was not mentioned elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…Actual contact of vaccine boxes with outer walls was not mentioned elsewhere. Regarding the type of refrigerator, ‘full-size dual-zone refrigerator/freezers (separate exterior doors)’ were used by 3% in our sample, compared to at least 44.4% of US physicians [16,28]. Pharmaceutical-grade refrigerators were used by 3.9% to 13.3% of Australian and US general practices, compared to 12.0% in our sample [28,29].…”
Section: Discussionmentioning
confidence: 99%